Gender and the city before modernity - Foxhall, Lin.; Neher, Gabriele (Chichester ; Malden, MA : Wiley Blackwell, 2012)
Gender and the city before modernity presents a series of multi-disciplinary readings that explore issues relating to the role of gender in a variety of cities of the ancient, medieval, and early modern worlds. Presents an inter-disciplinary collection of readings that reveal new insights into the intersection of gender, temporality, and urban space features a wide geographical and methodological range, includes numerous illustrations to enhance clarity.
Gender and the city before modernity; Contents; Notes on contributors; Introduction; 1 The queen and the city: royal female intervention and patronage in hellenistic civic communities; 2 'A remarkably patterned life': domestic and public in the Aztec household city; 3 women, property and urban space in tenth-century Milan; 4 Towards a female topography of the ancient Greek city: case studies from late archaic and early classical Athens (c.520-400 BCE); 5 Bodymaps: sexing space and zoning gender in ancient Athens.
"Originally published as Volume 23, Issue 3 of Gender & History."
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: To 1500; Women -- History -- To 1500.; Women -- Social life and customs; City and town life -- History -- To 1500.; Sociology, Urban -- History -- To 1500.; SOCIAL SCIENCE -- Women's Studies; City and town life; Sociology, Urban; Women; Women -- Social life and customs; Electronic books; History